Calmodulin‐mediated events during the life cycle of the amoebozoan Dictyostelium discoideum. (26th November 2019) - O'Day, Danton H.; Mathavarajah, Sabateeshan; Myre, Michael A.; Huber, Robert J.
ABSTRACT: This review focusses on the functions of intracellular and extracellular calmodulin, its target proteins and their binding proteins during the asexual life cycle of Dictyostelium discoideum . Calmodulin is a primary regulatory protein of calcium signal transduction that functions throughout all stages. During growth, it mediates autophagy, the cell cycle, folic acid chemotaxis, phagocytosis, and other functions. During mitosis, specific calmodulin‐binding proteins translocate to alternative locations. Translocation of at least one cell adhesion protein is calmodulin dependent. When starved, cells undergo calmodulin‐dependent chemotaxis to cyclic AMP generating a multicellular pseudoplasmodium. Calmodulin‐dependent signalling within the slug sets up a defined pattern and polarity that sets the stage for the final events of morphogenesis and cell differentiation. Transected slugs undergo calmodulin‐dependent transdifferentiation to re‐establish the disrupted pattern and polarity. Calmodulin function is critical for stalk cell differentiation but also functions in spore formation, events that begin in the pseudoplasmodium. The asexual life cycle restarts with the calmodulin‐dependent germination of spores. Specific calmodulin‐binding proteins as well as some of their binding partners have been linked to each of these events. The functions of extracellular calmodulin during growth and development are also discussed. This overview brings to the forefront the central role of calmodulin, working through its numerous binding proteins, as a primary downstream regulator of the critical calcium signalling pathways that have been well established in this model eukaryote. This is the first time the function of calmodulin and its target proteins have been documented through the complete life cycle of any eukaryote.